Narrative Structure and Local Wisdom Values in Muna Children's Stories: A Study of Pa Ode bhe Nosi and Kafotalo Kosibaribarihantomu: Struktur Naratif dan Nilai Kearifan Lokal dalam Cerita Anak Daerah Muna: Kajian Pa Ode Bhe Nosi dan Kafotalo Kosibaribarihantomu - Wa Ode Nirwana; Irianto Ibrahim; Saidiman; Nur Israfyan Sofian (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
This study aims to analyze the narrative structure and local wisdom values in two Muna children’s stories, namely Pa Ode bhe Nosi (Pak Ode dan Nosi) by Nurjannah Tamil and Kafotalo Kosibaribarihantomu (Kemenangan Bersama) by Rikar Karim. The study employs a library research design with a descriptive qualitative approach. The data consist of narrative excerpts, dialogues, and descriptions of events purposively selected from the two texts. Data collection was conducted through intensive reading, note-taking, coding, and classification based on William Labov’s narrative structure model, while local wisdom values were analyzed using qualitative content analysis. The findings reveal that both stories contain complete narrative components, namely abstract, orientation, complicating action, evaluation, resolution, and coda. Pa Ode bhe Nosi highlights the values of responsibility, care, affection, cultural honor, and commitment to preserving the traditional horse attraction performance, whereas Kafotalo Kosibaribarihantomu represents the values of mutual cooperation, perseverance, social care, friendship, and the preservation of the traditional game kalego. Both stories demonstrate that modern Muna children’s literature is not merely a medium of entertainment but also a text that organizes cultural values through coherent narrative patterns. This study offers a synthetic reading model that connects William Labov’s narrative structure with the transmission of local wisdom, thereby strengthening studies of regional children’s literature, character education, and the preservation of Muna culture.